Strategic management - Haslinda Abdullah Prof Dr (UPNM Press, Universiti Pertahanan Nasional Malaysia, 2016)
This book is written for undergraduate students to have the basic knowledge and understanding in strategic planning, formulation, implementation and evaluation not only in business